HPLC DETERMINATION OF D-PANTHENOL AND GLYCYRRHETINIC ACID FROM A HERBAL ANTI-HERPETIC SUPPLEMENT - Elena Gabriela Oltean; G. Oltean; C. Chiurciu (Medicamentul Veterinar, 2016)
HPLC was used for the quantitative determination of panthenol and glycyrrhetinic acid in an herbal antiherpetic supplement containing panthenol (B5 provitamin) and alcoholic extract of Glycyrrhiza glabra. For the determination of panthenol, the separation was carried out on a Kromasil 60-S Hilic D C18 column (250x4.6 mm, 5 µm), with methanol – 20 mM potassium phosphate dibasic, pH 6 (10:90, volume ratio) as the mobile phase. The detection wavelength was set at 210 nm. Flow was 1 mL·min-1 and the column temperature was maintained at (30±0.5) °C. For glycyrrhetinic acid, a Hypersil C18 BDS column (250x4.6 mm, 5 µm) with acetonitrile – 0.1% phosphoric acid in water (75:25, volume ratio) isocratic elution. The detection wavelength was set at 250 nm. Flow was 1 mL·min-1 and the column temperature was maintained at (30±0.5) °C.